A Look on the Wild Side - Zonta, Mario; Cabell, Walter Martyn (Flesh / Trash / Heat - The Wild Side of the Movies, 2004)
Mario Zonta's documentary opens with footage of Paul Morrissey, Holly Woodlawn and Joe Dallesandro on the red carpet at the Cannes Film Festival, where the Trilogy was receiving a special anniversary screening as part of a tribute to Morrissey, in May of 2002. Thereafter, the film is composed of Zonta's informal, off-the-cuff interviews with the three principals, interspersed with clips from the films. [www.joedallesandro.com]